Estimation of Vehicular Emissions of Major Districts in Kerala - Anil, Krishnanand; S. , Ghanashyam; A. , Suraj; E.T. , Rahul; Premkumar, Akhil; Nair, Rohan; S.N. , Jyothi; Prasad, Geena (International Journal of Psychosocial Rehabilitation, 2020)
Air pollution is of great importance in the current world, and it is a major factor affecting the health of the population. It is a major contributor to global warming too. Air pollution occurs due to many factors, such as pollutants from industrial and personal use. Among personal uses, vehicular transportation contributes the most to air pollution. The main objective of the current study is to have an understanding of the average amount of pollutants released into the atmosphere by different vehicular categories per day in the year 2018. Carbon Dioxide (CO2), Carbon Monoxide (CO), Nitrogen Oxide (NOx), Sulphur Dioxide (SO2), Hydrocarbons (HC), Methane (CH4), and Particulate Matter (PM) are the major contributors among the pollutants released into the atmosphere. This study shows the major vehicle categories that produce the most amount of pollution. The amount of pollutants released into the atmosphere in different districts varies. This study shows the category wise pollution released into the atmosphere in major cities of Kerala